Personal values as predictors of identity formation among Nigerian University students - Iyanuoluwa, Adebo Adetumilara; Hamsan, Hanina Halimatusaadiah; Abdullah, Haslinda; Ahmad, Nobaya (Human Resource Management Academic Research Society, 2021)
University environments provide atmospheres where young adults can explore Identity alternatives, make Identity commitments, and internalize various values required for adult life before graduation. Previous studies have demonstrated the relationship between values and Identity using Identity process theory. The current study explores this relationship using the Identity status paradigm. Particularly it examines the effects of self-direction, ideal body internalization, and materialistic value orientation on Identity exploration and commitment in a sample of 52 University students. This however is a preliminary exploration of values and identity issues within a broader study. The study utilized a cross-sectional design. Data shows that majority of the participants (84.9%) fall into the low exploration category, while less than half (44.2%) fall into the low commitment category. Also, no differences were found in students identity statuses based on their gender and age groups. Two separate Logistic regression analyses were performed. Result of the commitment model shows that Materialistic value orientation is a significant predictor of low Identity commitment and an increase in Self-direction reduces the probability of low Identity commitment, while the Identity exploration model shows an ascending predicted probability of values and low Identity exploration.